Letters (and the art of storytelling). - Yap, Shawn Kai Siang. (2012)
The project is a study and exploration of narrative patterns and methods, and culminates in a short story titled "Letters". Letters follows a boy as he searches for and finds God in the strangest of places; letters sent through a drawer of an old desk in his room. At the heart of it, It is really a story about the permanent things in life; love, faith and hope. Even as the world – the boy included – changes with the passage of time, the old desk remains the same; a representation of the stoic and steadfast relationship established between boy and God. Letters hopes to redirect us to these things which truly deserve our attentions as we re-evaluate our lives .